2004
DOI: 10.1017/s0031182003004694
|View full text |Cite
|
Sign up to set email alerts
|

Lyme borreliosis in Europe and North America

Abstract: Since the discovery of the Lyme disease spirochete in North America in 1982 and in Europe in 1983, a plethora of studies on this unique group of spirochetes that comprise Borrelia burgdorferi sensu lato has been accumulated. In an attempt to compare and contrast Lyme borreliosis in Europe and North America we have reviewed the biology of the aetiologic agents, as well as the clinical aspects, diagnosis and treatment of this disease on both continents. Moreover, we have detailed the ecology of the Ixodes ticks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
233
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(242 citation statements)
references
References 298 publications
(325 reference statements)
6
233
0
3
Order By: Relevance
“…However, we found the opposite effect to that predicted for rainfall or humidity: questing nymphs were more likely to be present at times of low relative humidity and questing nymphs were more abundant in areas with lower annual rainfall. In general, previous studies have found that tick questing activity increases with increasing humidity (Randolph et al 2000;Piesman and Gern, 2004), but it might be that conditions can be too wet for ticks (e.g. they tend to quest less in the rain).…”
Section: Questing Nymph Abundancementioning
confidence: 94%
“…However, we found the opposite effect to that predicted for rainfall or humidity: questing nymphs were more likely to be present at times of low relative humidity and questing nymphs were more abundant in areas with lower annual rainfall. In general, previous studies have found that tick questing activity increases with increasing humidity (Randolph et al 2000;Piesman and Gern, 2004), but it might be that conditions can be too wet for ticks (e.g. they tend to quest less in the rain).…”
Section: Questing Nymph Abundancementioning
confidence: 94%
“…erythema migrans, facial palsy and major joint arthralgia), exposure to vector ticks in endemic areas and serological diagnostic tests (Aguero-Rosenfeld et al, 2005). It is well recognized that B. burgdorferi sl spirochaetes cause a variety of clinical symptoms (Piesman & Gern, 2004;Rizzoli et al, 2011), overlap geographically (Margos et al, 2011(Margos et al, , 2012 and exhibit differential reactivity with current serological diagnostic tests (Branda et al, 2013;Norman et al, 1996). Initial diagnostic tests (ELISAs and IgM/IgG immunoblots) were designed based on the B. burgdorferi ss organism; however, with our increased understanding of the genetic diversity of this species complex, many of these tests are proving to be less effective in their diagnostic abilities in areas where multiple Borrelia species are implicated in human disease (Dressler et al, 1994;Hauser et al, 1997Hauser et al, , 1998aNorman et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This species complex (also referred to as Lyme borreliosis group of spirochaetes) comprises parasitic bacteria that are maintained in natural transmission cycles between vector ticks of the genus Ixodes and numerous vertebrate reservoir hosts (Piesman & Gern, 2004). Members of the species complex are distributed throughout the temperate zones of the Northern Hemisphere.…”
mentioning
confidence: 99%